Investigation of hypertensive arteriopathy-related and cerebral amyloid angiopathy-related small vessel disease scores in patients from a memory clinic: a prospective single-centre study. Issue 4 (8th April 2021) - Matsuda, Kana; Shindo, Akihiro; Ii, Yuichiro; Tabei, Ken-ichi; Ueda, Yukito; Ishikawa, Hidehiro; Matsuura, Keita; Yoshimaru, Kimiko; Taniguchi, Akira; Kato, Natsuko; Satoh, Masayuki; Maeda, Masayuki; et al.
Abstract : Objective: The severity of cerebral small vessel disease (SVD) is assessed through neuroimaging findings, including hypertensive arteriopathy (HA)-SVD and cerebral amyloid angiopathy (CAA)-SVD. HA-SVD and CAA-SVD have been collectively estimated as total scores: the HA-SVD and CAA-SVD scores, respectively. Previous reports suggest that HA-SVD scores are associated with cognitive function; however, the relationship between CAA-SVD scores and cognitive function remains unclear. Therefore, we examined the association between CAA-SVD scores and cognitive function. Furthermore, we developed a modified CAA-SVD score considering cortical microinfarcts and posterior dominant white matter hyperintensities, which are imaging findings of CAA, and examined the association between these scores and cognitive function in the same patient group. Design: Prospective study. Setting: Single centre study from a memory clinic. Participants: Subjects were diagnosed with mild cognitive impairment (MCI) or mild dementia in our memory clinic between February 2017 and July 2019 and underwent clinical dementia rating scale and brain MRI assessment. A total of 42 patients (aged 75.3±9.12 years) were registered prospectively. Primary and secondary outcome measures: We evaluated intellectual function, memory, frontal lobe function and constructional ability. Furthermore, the relationship between each score and cognitive function was examined. Results: The CAA-SVD score showed significant associations with cognitive function (R 2 =0.63, p=0.016), but the HA-SVD score did not (R 2 =0.41, p=0.35). The modified CAA-SVD score was also significantly associated with cognitive function (R 2 =0.65, p=0.008). Conclusion: Cognitive function is associated with the CAA-SVD score, and more efficiently with the modified CAA-SVD score, in memory clinic patients. Although we have not validated the weighting of the modified CAA-SVD score, these scores can be a predictor of cognitive deterioration in patients with MCI and mild dementia.